Foot-and-mouth disease - Charbonnier, G.; Launois, M. (CTA / CIRAD, 2011)
This popular handbook aims to communicate a wider understanding of the most important concepts of this highly contagious, viral disease. It takes an original approach by presenting different points of view, from those of livestock farmers and veterinarians in developed and developing countries, to a journalist and an economist, as well as including – with humour – those of cows, the virus and the vaccine.